Social Interactions of TB Patients at Helvetia Community Health Center in Medan - Elis Anggeria; Yosni Yohana Sipayung; Kristin Mei Sara Zebua (Talenta Publisher, 2021)
Social interaction is a relationship between humans, both in individuals and in groups. Social interaction in society occurs because of social contact and communication. Pulmonary TB is an infectious disease caused by Mycobacterium tuberculosis. This study aimed to determine the social interaction of pulmonary tuberculosis patients at Helvetia Community Health Center in Medan. This study used a descriptive design. The population in this study were all patients suffering from pulmonary tuberculosis. The sample size was determined using a purposive sampling technique, and it was found that the sample size was 33 respondents. The data collection used observation form. The data analysis used frequency distribution. The result shows various respondents' characteristics. The majority were 29-43 years old, male, high school educated, self-employed, and have suffered from TB â‰¤ 3 years. Based on the study result, 25 of 33 sample patients with pulmonary tuberculosis still interacted socially with their community. The conclusion is that patients with pulmonary tuberculosis still socially interact with the community in their neighborhood.